1969
DOI: 10.1093/bja/41.4.317
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcuronium and Tubocurarine on Blood Pressure and Heart Rate: A Clinical Comparison

Abstract: The effects of alcuronium (0.15 and 0.3 mg/kg) and tubocurarine (0.3 and 0.6 mg/kg) on arterial pressure and heart rate and rhythm have been compared in forty patients during nitrous oxide, oxygen and pethidine anaesthesia and in twenty patients during nitrous oxide, oxygen and halothane anaesthesia, prior to surgery. When halothane was used only the smaller doses of relaxants were given. Patients were divided into six homologous groups of ten patients. Both relaxants caused a fall in arterial pressure which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Mean arterial pressure was little affected by alcuronium, a finding in keeping with the work of Tammisto and Welling (1969). Marked falls of blood pressure have been reported by other workers (Hunter, 1964;Baraka, 1967).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Mean arterial pressure was little affected by alcuronium, a finding in keeping with the work of Tammisto and Welling (1969). Marked falls of blood pressure have been reported by other workers (Hunter, 1964;Baraka, 1967).…”
Section: Discussionsupporting
confidence: 87%
“…Stovner and Lund (1964) found that heart rate increased by up to 20 beats/min after administration of alcuronium (0.20-0.25 mg/kg); these measurements were made, however, at the time of endotracheal intubation, a procedure well known to cause tachycardia (Rollason and Hough, 1957). Tammisto and Welling (1969) found an increase of heart rate following administration of alcuronium in a dose of 0.15 mg/kg, and a greater effect with twice this dose.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, alcuronium seemed to give more complete protection against suxamethonium-induced bradycardia than tubocurarine. During anaesthesia a larger dose (0.15 mg/kg) of alcuronium has also been found to cause a moderate increase in heart rate (TAMMISTO & WELLING 1969). In the light of our present knowledge, it can only be supposed that alcuronium exerts a vagolytic effect similar to that of gallamine ( RIKER & WESCOE 195 1 ) .…”
Section: Discussionmentioning
confidence: 91%
“…However, it does not appear to have been used in patients undergoing renal transplantation, or in patients with chronic renal failure. Specificity of action, minimal cardiovascular effects (Canak, 1965;Tammisto and Welling, 1969;Kennedy and Kelman, 1970) excellent relaxation and easy reversibility (Foldes et al, 1963) have prompted us to use the drug in patients with end-stage renal failure undergoing transplantation and its use forms the basis of this report.…”
mentioning
confidence: 99%